2015
DOI: 10.3390/ijerph120606455
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Relationship between Outdoor Time and Physical Activity, Sedentary Behaviour, and Physical Fitness in Children? A Systematic Review

Abstract: The objective of this systematic review was to examine the relationship between outdoor time and: (1) physical activity, (2) cardiorespiratory fitness, (3) musculoskeletal fitness, (4) sedentary behaviour; or (5) motor skill development in children aged 3–12 years. We identified 28 relevant studies that were assessed for quality using the GRADE framework. The systematic review revealed overall positive effects of outdoor time on physical activity, sedentary behaviour, and cardiorespiratory fitness, although ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
239
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(310 citation statements)
references
References 75 publications
(228 reference statements)
23
239
0
11
Order By: Relevance
“…In a previous investigation among 7-14 year olds, each additional hour spent outdoors was associated with 7.0 more minutes of daily MVPA and 762 more steps/day. 19 Our findings are also in OUTDOOR TIME AND PHYSICAL ACTIVITY agreement with a recent systematic review that concluded that children who spend more time outdoors are more active overall, 9 and with a recent position statement on active outdoor play. 12 Consistent with previous research, we found that boys 5-6 years of age were more active than their female counterparts and that low family income was associated with reduced odds of meeting PA guidelines.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In a previous investigation among 7-14 year olds, each additional hour spent outdoors was associated with 7.0 more minutes of daily MVPA and 762 more steps/day. 19 Our findings are also in OUTDOOR TIME AND PHYSICAL ACTIVITY agreement with a recent systematic review that concluded that children who spend more time outdoors are more active overall, 9 and with a recent position statement on active outdoor play. 12 Consistent with previous research, we found that boys 5-6 years of age were more active than their female counterparts and that low family income was associated with reduced odds of meeting PA guidelines.…”
Section: Discussionsupporting
confidence: 77%
“…9,19 For example, among 7-14 year olds who participated in the 2012-2013 CHMS, each additional hour spent outside was associated with 13 fewer minutes of SED/day. 19 We also found no relationship between outdoor time and PA among 3-4 year olds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garapen motoreari dagokionez, kanpo espazioak baimentzen du orekaren eta giharren lanketa, bertan aukera egon ohi delako oztopoen gainetik salto egiteko, materialak jasotzeko eta botatzeko eta ontziak edo beste material batzuk betetzeko (Early Head Start National Resource Center, 2013;Fjortoft 2004Fjortoft , 2001Gray, et al, 2015).…”
Section: Kanpo Erabilerak Haurraren Ongizatean Dituen Onurakunclassified
“…Questionnaire surveys are relatively popular as they enable easy data acquisition from a large number of respondents. However, overvaluation in subjective answer evaluation might present a certain disadvantage (Gray et al, 2015).For this reason, some instrument-based PA measurement methods can be deemed optimal. Due to simplicity and sufficient validity of results (Crouter et al, 2013;Rothney et al, 2008), we have selected triaxial accelerometers as the most suitable for our study.…”
Section: Introductionmentioning
confidence: 99%